Pengaruh Dimensi Komunikasi Dan Motivasi Kerja Terhadap Efektivitas Pencapaian Target Pajak Bumi Dan Bangunan (PBB) - Engkus Kurniawan; Oyon Saryono; Irma Darmawati (CV. Aksara Global Akademia, 2025)
The problem in this study is how the influence of the dimensions of communication and work motivation on the effectiveness of achieving PBB target at the Banjar District Office, Banjar City. This research was conducted using survey and explanatory analysis methods, namely explaining and analyzing the magnitude of the influence of the dimensions of communication and motivation on the effectiveness of achieving the target of PBB. The population in this study were all employees at the Banjar District Office, Banjar City, with a total of 64 employees. The results of the study show that the communication dimension has a positive effect on the effectiveness of achieving PBB targets. Motivation has a positive effect on the effectiveness of achieving PBB targets. The effectiveness of achieving PBB targets is positively influenced by the dimensions of communication and motivation, this means that the better the dimensions of communication and motivation, the more effective the effectiveness of achieving PBB targets will be